2012
DOI: 10.1143/apex.5.055102
|View full text |Cite
|
Sign up to set email alerts
|

Highly Uniform Thin-Film Transistors Printed on Flexible Plastic Films with Morphology-Controlled Carbon Nanotube Network Channels

Abstract: Carbon nanotube (CNT) transistor arrays were fabricated on plastic films by printing. All the device elements were directly patterned by maskless printing without any additional patterning process, and minimum materials were used. During fabrication, the morphology of the CNT random network was controlled by an adsorption mechanism on the surface to be printed, which resulted in excellent and uniform electrical properties. The field-effect mobility was further improved by post-treatment to modify the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…17 For the SWCNTs with a 1.3 nm diameter, the extraction of the s-SWCNT fraction was carried out based on the electric-field-induced layer formation (ELF) technique, 11 which is an electrophoresis method. Semiconducting chiralities in the used SWCNTs observed by the photoluminescence mapping measurement (Horiba Spex, Fluorolog 3-2 TRIAX) were as follows: (8,6), (8,7), (9,7), (9,8), (10,5), (10,6), (10,8), (10,9), (11,3), (11,4), (11,6), (11,7), (11,9), (12,1), (12,4), (12,5), (12,7), (12,8), (13,2), (13,3), (13,5), (13,6), (14,1), and (14,3). The purity o...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 For the SWCNTs with a 1.3 nm diameter, the extraction of the s-SWCNT fraction was carried out based on the electric-field-induced layer formation (ELF) technique, 11 which is an electrophoresis method. Semiconducting chiralities in the used SWCNTs observed by the photoluminescence mapping measurement (Horiba Spex, Fluorolog 3-2 TRIAX) were as follows: (8,6), (8,7), (9,7), (9,8), (10,5), (10,6), (10,8), (10,9), (11,3), (11,4), (11,6), (11,7), (11,9), (12,1), (12,4), (12,5), (12,7), (12,8), (13,2), (13,3), (13,5), (13,6), (14,1), and (14,3). The purity o...…”
Section: Methodsmentioning
confidence: 99%
“…3 For the printed electronics of SWCNTs, various processes, not only the printing process itself, but also the semiconducting-ink preparation and removal of surfactants by heat and/or wet treatments, are required. 4 Among these processes, recent significant advances in the extraction techniques for the ink preparation of semiconducting SWCNTs (s-SWCNTs), such as dielectrophoresis, 5 density-gradient ultracentrifugation, 6 DNA separation, 7 and gel-based extraction 8 have improved the device performance of thin-film transistors of SWCNTs (SWCNT-TFTs). Although most of the reported extraction methods need to use ionic surfactants to disperse SWCNTs, it is well known that ionic contaminations can degrade device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Carrier doping processes to achieve complementary metal oxide semiconductor (CMOS) circuits are also compatible with liquid‐phase fabrication 139, 140. However, it is usually difficult to form a uniform film by printing,141 though H. Mumata et al reported highly uniform printed CNT thin‐film transistors produced by an adsorption mechanism 142…”
Section: Fabrication Techniques For Flexible Thin‐film Transistorsmentioning
confidence: 99%
“…More reproducible casting techniques, for example, spray printing, will likely allow for better control of film thickness in future implementations. 28,29 Nonetheless, all the FETs demonstrate relatively stable performance up to 80% strain.…”
mentioning
confidence: 96%